Praktik dan Edukasi Integritas Anti Korupsi dalam Pemanfaatan Dana Desa di Nagari Panyakalan, Kabupaten Solok - Tengku Rika Valentina; Roni Ekha Putera; Ria Ariany; Kusdarini Kusdarini (Warta Pengabdian Andalas, 2019)
In terms of utilization of village funds, if examined more deeply in the period of 2015-2019, the central government has allocated village funds worth Rp.46.9 trillion, double the previous year which was only Rp20 trillion. The village funds were then allocated to 74,754 villages spread across Indonesia, and each village received village funds ranging from Rp. 600 million to Rp. 800 million. Interestingly, based on preliminary data from Indonesia Corruption Watch (ICW), from 2015 to Semester I 2018, cases of corruption in village funds have increased, there are approximately 181 cases of corruption in village funds with 184 corruption suspects and a loss of Rp 40.6 billion. There are three assumptions arising from the above data findings, namely (1) there are cultural factors that are supported by the foundation of social norms that emphasize patron-client joints and negative symbiotic-mutualism relationships between village elites and local groups of village communities; (2) weak institutionalization of political institutionalization at the village level, where bribe money is the norm in establishing a development project; (3 The management of village institutional institutions after the issuance of Law No. 6/2014 on Villages, is not comparable with the ability of local elites and government at the local level in describing the reality of development and community empowerment, so that it continues to grow the oligarchic practices of elite power that has traditional authority which is wrong One trigger for corruption The solution offered is the Procurement Team from Andalas University conducting training to Nagari officials in Nagari Panyakalan, Solok Regency, on how to build Anti-Corruption Integrity in the utilization of village funds and then the Penggal Team in collaboration with the Nagari Apparatus, the Nagari Deliberation Board (BMN) ) helped initiate the formation of an anti-corruption monitoring group in the nagari.